2010
DOI: 10.1042/bst0381342
|View full text |Cite
|
Sign up to set email alerts
|

Complement factor H and age-related macular degeneration: the role of glycosaminoglycan recognition in disease pathology

Abstract: AMD (age-related macular degeneration) is the major cause of blindness in the western world, associated with the formation of extracellular deposits called drusen in the macula, i.e. the central region of the retina. These drusen contain cellular debris and proteins, including components of the complement system such as the regulator CFH (complement factor H); dysregulation of complement is thought to play a major role in the development of AMD. CFH acts through its capacity to recognize polyanionic structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 57 publications
0
84
0
Order By: Relevance
“…In the brain, IgG might act as a selfprotecting factor via a mechanism of enhancing microglial endocytosis and release of TNF-a or by neutralizing complement factors [14,15]. In the eye, a prolongation of the brain, TNF-a and the activation of the complement cascade play a key role in pathogenesis of age-related macular degeneration (AMD), the leading cause of blindness in people over 50 in the Western world [16][17][18]. As in the brain, IgG may also function as a self-protecting factor and be involved in the development of AMD.…”
Section: Introductionmentioning
confidence: 99%
“…In the brain, IgG might act as a selfprotecting factor via a mechanism of enhancing microglial endocytosis and release of TNF-a or by neutralizing complement factors [14,15]. In the eye, a prolongation of the brain, TNF-a and the activation of the complement cascade play a key role in pathogenesis of age-related macular degeneration (AMD), the leading cause of blindness in people over 50 in the Western world [16][17][18]. As in the brain, IgG may also function as a self-protecting factor and be involved in the development of AMD.…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested that tissue specificity of these CFH-binding molecules may be important in the pathology of the disease, and in separating the mechanism of AMD from other CFH-related diseases, such as renal dense-deposit disease. 58 This study did not examine binding at the other GAG binding part of CFH, SCRs 18-20, which are duplicated in CFHR1. The risk variant 402H binds less well to monomeric CRP, an opsonin, resulting in less protection by CFH on necrotic or apoptotic self-tissues in the retina.…”
Section: Genetic Variants Of Complement Genes Associated With Amd Andmentioning
confidence: 99%
“…(Clark et al, 2010;Clark et al, 2013;Kazatchkine et al, 1979;Schmidt et al, 2008b;Zaferani et al, 2012) We found that CsA treatment led to reduction of CFH binding to the surface of endothelial cells and impaired CFH surface cofactor activity. We therefore assessed whether CsA treatment affected the endothelial cell glycocalyx (consisting of glycosaminoglycans and sialic acid residues) by staining with an Alexa Fluor 594-conjugated wheat germ agglutinin (Thermo Fischer Scientific, W11262, dilution 1:500) which binds to sialic acid and N-acetylglucosaminyl residues, and live cell imaging.…”
Section: D) Cofactor Activity Of Cfh On Surface Of Neuraminidase-treamentioning
confidence: 99%
“…Surface cofactor activity of CFH requires its binding to EC surfaces via glycosaminoglycans or sialic acid clusters. (Clark et al, 2010;Clark et al, 2013;Kazatchkine et al, 1979;Schmidt et al, 2008b;Zaferani et al, 2012) We tested this by pre-treating BOECs to neuraminidase which cleaves sialic acid groups from the glycocalyx of endothelial cells. (Libby et al, 1986) When BOECs were pre-incubated with neuraminidase 500 mU/mL for 1 hour followed by CFH for 1 hour, prior to being thoroughly washed and incubated with C3b and CFI at 37 degrees Celsius, degradation products were detectable only after 60 minutes (Figure 3.9C).…”
Section: Cyclosporine Treatment Led To Impaired Complement Factor H Smentioning
confidence: 99%
See 1 more Smart Citation